Avaliação da política pública de inclusão digital: construindo uma trajetória do Projeto UCA (Um Computador por Aluno) com os gestores em Fortaleza - Souza, Geisamara de Oliveira (2015)
This work aims to evaluate the policy of digital inclusion in education with a focus on cost laptops - One Laptop per Child, in Fortaleza / Ceará. Aims to understand from the managers of the project experience, as is the trajectory of the project in its three phases, and to what extent, the UCA leads to digital inclusion. From the perspective of a comprehensive evaluation (LEJANO, 2006), we list the analytical category of digital inclusion, from the thought Warschauer (2006), which considers overcoming the digital divide, not only with the supply of machinery and connectivity (resources physical), but promotes a process of social inclusion, from the relationship between the digital, social and human resources. Therefore, we carried out an evaluation research focused research focused on the managers of the three institutions involved in the project, the Federal University of Ceará, the City Department of Education and the Municipal School Rubem Alves, in the period 2010 to 2014. The evaluation shows that the trajectory of the UCA, as a policy of digital inclusion, distribution of equipment as a way of overcoming the digital divide is performed, however, the attempt to establish itself as a socio-political inclusion digital, to Warschauer (2006), needs to be improved because of that there is the practice of discontinuity of public policies related to the governments that cause disruptions to social and digital inclusion process and interfere in the processes of physical, digital, human and social, so this evaluation, realize the limits of UCA.